2018
DOI: 10.1002/pon.4938
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability, and safety of the Recapture Life videoconferencing intervention for adolescent and young adult cancer survivors

Abstract: Objective: Online psychological therapies provide a way to connect adolescent and young adult (AYA) cancer survivors to evidence-based support. We aimed to establish the feasibility, acceptability, and safety of Recapture life, a six-session group-based online cognitive-behavioural intervention, led by a facilitator, for AYAs in the early post-treatment period.Methods: A randomised-controlled trial compared Recapture Life to an online peer-support group control and a waitlist control. Participants could nomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 36 publications
1
59
0
Order By: Relevance
“…Importantly, study findings provide a more comprehensive understanding of the distress experienced by the population than existing models, by integrating data from different sources (e.g., case formulations, clinical notes). As such, study results have important clinical implications for further developing psychological support for the population and expand the growing literature on CBT-based interventions for the population (Campo et al, 2017;Sansom-Daly et al, 2018). However, it should be noted that only 10 participants were recruited raising concerns regarding the feasibility and acceptability of individualized CBT for the population.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Importantly, study findings provide a more comprehensive understanding of the distress experienced by the population than existing models, by integrating data from different sources (e.g., case formulations, clinical notes). As such, study results have important clinical implications for further developing psychological support for the population and expand the growing literature on CBT-based interventions for the population (Campo et al, 2017;Sansom-Daly et al, 2018). However, it should be noted that only 10 participants were recruited raising concerns regarding the feasibility and acceptability of individualized CBT for the population.…”
Section: Discussionmentioning
confidence: 77%
“…Key characteristics were worry about the future and fear of cancer recurrence, causing decisional anxiety and depressive as well as existential rumination. Indeed, other research has shown AYA cancer survivors to imagine their future in more illness focused and overgeneralized way, in comparison to AYAs without cancer (Sansom-Daly et al, 2018). Given adaptive problem solving and goal setting are associated with the ability to imagine future events more specifically (Schacter, Addis & Buckner, 2007) such overgeneralized thinking may be an important target for psychological interventions for the AYA cancer survivor population (Sansom-Daly et al, 2018).…”
Section: Worry and Ruminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using examples from our research, ethics‐related delays have meant that some AYA living in rural/remote Australia missed out on the opportunity to access evidence‐based, online psychological treatment in survivorship and AYA with uncertain/unfavourable cancer prognoses did not receive the opportunity to access an age‐appropriate advance‐care planning tool to guide them through challenging end‐of‐life conversations …”
mentioning
confidence: 99%